PENERAPAN EVIDENCE BASED NURSING KOMPRES HANGAT TERHADAP PENURUNAN SUHU TUBUH PADA ANAK DEMAM DI RSPAD GATOT SOEBROTO - Nur Sari Dewi (2023)
Fever is a condition where there is an increase in body temperature reaching> 37.5⁰C. High fever that is not treated immediately will be dangerous for children and cause febrile seizures and can even lead to brain tissue hypoxia and lead to brain damage. Management that is often carried out in cases of children with fever to reduce body temperature includes pharmacological and non-pharmacological management. One of the non-pharmacological management of children with fever is warm compress therapy. Giving warm compresses to large blood vessels provides stimulation to the preoptic area of the hypothalamus so that body temperature can decrease. This study aims to analyze the effect of warm compresses on decreasing body temperature in children with fever in the hospital. This study used experimental research with a pre-post test sign design. The samples used were managed patients and resumed patients who had a fever for 3 days. Warm compresses are given for 10-15 minutes in the axilla. Data collection was carried out using observation sheets and measuring body temperature. The results showed that there was a decrease in body temperature after applying warm compresses with an average decrease in temperature of 0.4⁰C. The application of this Warm Compress intervention has a positive impact on children with fever, namely a decrease in the child's body temperature every day. Hospitals can apply this method as a non-pharmacological therapy to reduce fever in children. Key Words: Decreased Body Temperature, Fever, Warm Compresses